Necklace‐embedded electrocardiogram for the detection and diagnosis of atrial fibrillation. Issue 5 (25th February 2021) - Santala, Onni E.; Lipponen, Jukka A.; Jäntti, Helena; Rissanen, Tuomas T.; Halonen, Jari; Kolk, Indrek; Pohjantähti‐Maaroos, Hanna; Tarvainen, Mika P.; Väliaho, Eemu‐Samuli; Hartikainen, Juha; Martikainen, Tero
Abstract: Background: Atrial fibrillation (AF) is the major cause of stroke since approximately 25% of all strokes are of cardioembolic‐origin. The detection and diagnosis of AF are often challenging due to the asymptomatic and intermittent nature of AF. Hypothesis: A wearable electrocardiogram (ECG)‐device could increase the likelihood of AF detection. The aim of this study was to evaluate the feasibility and reliability of a novel, consumer‐grade, single‐lead ECG recording device (Necklace‐ECG) for screening, identifying and diagnosing of AF both by a cardiologist and automated AF‐detection algorithms. Methods: A thirty‐second ECG was recorded with the Necklace‐ECG device from two positions; between the palms (palm) and between the palm and the chest (chest). Simultaneously registered 3‐lead ECGs (Holter) served as a golden standard for the final rhythm diagnosis. Two cardiologists interpreted independently in a blinded fashion the Necklace‐ECG recordings from 145 patients (66 AF and 79 sinus rhythm, SR). In addition, the Necklace‐ECG recordings were analyzed with an automatic AF detection algorithm. Results: Two cardiologists diagnosed the correct rhythm of the interpretable Necklace‐ECG with a mean sensitivity of 97.2% and 99.1% (palm and chest, respectively) and specificity of 100% and 98.5%. The automatic arrhythmia algorithm detected the correct rhythm with a sensitivity of 94.7% and 98.3% (palm and chest) and specificity of 100% of the interpretable measurements. Conclusions: The novel Necklace‐ECG device is able to detect AF with high sensitivity and specificity as evaluated both by cardiologists and an automated AF‐detection algorithm. Thus, the wearable Necklace‐ECG is a new, promising method for AF screening. Clinical trial registration: Study was registered in the ClinicalTrials.gov database (NCT03753139).